An Energy Efficient Clustering Algorithm for Wireless Sensor Networks (EECA) - Zawaideh, Firas (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: Energy conservation has a main priority in all technology and engineering field. Most current applications that consume energy can be customized or optimized in a process resulting less energy consumption. During the rise of wireless sensors field applications, and also, the critical situation of energy consumption, the optimization of energy dispatch becomes a critical and important field of research. Hence, the wireless sensor depends on its internal battery to work its total life time, extending the life time by minimizing the consumption of power is also very important field in current researches. This research aims to optimize the energy consumption of wide scale wireless sensor networks by deploying a novel and adaptive improvement and modification on the traditional clustering of the cells of the network. In this thesis we work on load balancing of each cell in the network, introduce the “Potential” concept which is a measurement of node and cells overall availability and it is related to energy, distance and data transfer, deal with the nodes in between two clusters and finallymake all nodes die almost at the same time by using an adaptive system for solving these problems. This research improves the energy conservation with 93% regards to the original LEACH Algorithm. The results are shown and compared to the old LEACH, LEACH-M, and LEACH-L approaches, and this proposed algorithm will be named Energy Efficient Clustering Algorithm “EECA”. Keywords: Wireless sensors networks, sensors clustering, LEACH, fuzzy logic. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Enerji tasarrufu tüm teknoloji ve mühendislik alanlarında öncelikli bir konu olarak karşımıza çıkmaktadır. Güncel uygulamaların birçoğu ihtiyaca göre uyarlanan, en iyi şekilde kullanılabilen ve daha az enerji tüketimi sağlayacak enerji harcama öğelerini içerir. Kablosuz algılayıcıların alan uygulamalarında olan artış süresince, hassas bir konu olan enerji tüketimi ve enerji dağılımını en iyi şekilde sağlamak önemli ve öncelikli bir araştırma konusu olarak karşımıza çıkmaktadır. Kablosuz algılayıcıların çalışma süresinin içte olan piline bağlı olmasından dolayı, bu algılayıcıların yaşam süresini harcadıkları enerji miktarını azaltarak daha etkili çalışmasını sağlamak güncel araştırma konuları içinde çok önemli bir alanı kapsamaktadır. Bu araştırma her hücrenin yük dengeleme üzerinde çalışmak, düğüm ve hücrelerin genel durumu bir ölçüsüdür "Potansiyel" kavramının tanıtılması ve enerji, mesafe ve veri transferi, iki küme arasında ve nihayet düğümleri ile anlaşma ile ilgilidir bu sorunların çözümü için bir adaptif sistem kullanılarak en iyi duruma getirmeyi amaçlamaktadır. Enerji korumasını yüzde 93 oranında iyileştirmeyi amaçlayan bu araştırma, aynı zamanda ağın farklı hücrelerinin iletişimsel olarak aktarılmasının dengesizliği sorununa da değinmekte ve bu sorunun çözümü için bir sistem önermektedir. Araştırma bulguları önceki LEACH, LEACH-M ve LEACH-L yaklaşımlarıyla karşılaştırılmıştır. Anahtar Kelimeler: Kablosuz algılayıcı ağları, algılayıcı kümeleri, LEACH, bulanık mantık.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2012. Supervisor: Assoc. Prof. Dr. Muhammed Salamah.
Keywords: Computer Engineering; Computer Networks; Wireless Sensor Networks; Wireless Sensors Networks - Sensors Clustering - LEACH - Fuzzy Logic